2000
DOI: 10.1021/ja0020207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Ions on the Electronic, Redox, and Catalytic Properties of Cofactor TTQ of Quinoprotein Amine Dehydrogenases

Abstract: Model compounds of novel organic cofactor TTQ (tryptophan tryptophylquinone) of quinoprotein methylamine and aromatic amine dehydrogenases have been shown to interact with a series of metal ions in anhydrous organic media. Spectroscopic analyses including UV−vis, NMR, and resonance Raman indicate that the metal ion binds to the TTQ model compounds at their o-quinone moiety, the binding mode of which is similar to that proposed for the interaction between cofactor TTQ and a cationic species in the native enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Substantial mechanistic information has been obtained through catalytic aerobic deamination of benzylamine mediated by synthetic models of natural quinones which confirm the occurrence of the transamination mechanism 7. However, these models failed to oxidize unactivated primary aliphatic amines under the same experimental conditions, with the exception of a recent study showing that the metal ion complex of the TTQ model compound was able to oxidize aliphatic amines in anhydrous organic media, whereas no reaction took place in the absence of the metal ion 8…”
Section: Methodsmentioning
confidence: 99%
“…Substantial mechanistic information has been obtained through catalytic aerobic deamination of benzylamine mediated by synthetic models of natural quinones which confirm the occurrence of the transamination mechanism 7. However, these models failed to oxidize unactivated primary aliphatic amines under the same experimental conditions, with the exception of a recent study showing that the metal ion complex of the TTQ model compound was able to oxidize aliphatic amines in anhydrous organic media, whereas no reaction took place in the absence of the metal ion 8…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, no reaction took place in the absence of the metal ion. [9] A few years ago, we showed that electrogenerated o-azaquinone 1 ox (Scheme 1) acted as an effective biomimetic catalyst for the oxidation of benzylamine under metal-free conditions, through the pyridoxal-like transamination process reported for amine oxidase cofactors. The catalytic cycle produced the reduced catalyst 1 red and N-benzylidenebenzyl-A C H T U N G T R E N N U N G amine as the product of amine oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The Lewis acidity of metal ion has been shown to control not only the electron-transfer step, but also the subsequent chemical step in the overall redox reactions. There are more examples for the catalytic control of electron-transfer reactions of metal ions, other than those described in this article [30][31][32][33]. There still remains a wealth of important fundamen- tal questions with regard to catalytic control of electron-transfer reactions, which have been only partially explored so far, and which certainly deserve much more detailed attention in the future.…”
Section: Discussionmentioning
confidence: 94%